Mechanism Study on the Preventive Effect of ELITEA Compound Tea on Hyperuricemia in Rats Based on Serum Untargeted Metabolomics - Shulian Liu; Yongliang Zhu; Wenjiong Wang; Xianghan Zhang; Linrui Gao; Xiangjun Qiu (Metabolites)
Background/Objectives: Hyperuricemia (HUA) has become the second largest metabolic disease after diabetes, and has become a major public health problem. The ELITEA compound tea extract can effectively reduce the serum uric acid level in HUA rat models. In this study, the mechanism of ELITEA compound tea on HUA was analyzed through serum untargeted metabolomics analysis. Methods: The rat model of HUA was established by feeding rats with a high uric acid diet. A total of 24 male SD rats were divided into a blank control group, a hyperuricemia model group, and an ELITEA compound tea prevention experimental group. UPLC-MS/MS was used to detect changes in metabolites in the blood of the three groups of rats, in order to identify potential biomarkers and study the mechanism of ELITEA compound tea in preventing HUA. Results: The ELITEA compound tea exhibited significant preventive effects on HUA rats. The analysis results showed that after ELITEA combined tea intervention, the 257 metabolites downregulated in the HUA model group showed an upward trend. Meanwhile, the 115 metabolites upregulated in the HUA model group showed a decreasing trend. Six main enrichment pathways were obtained, including arginine biosynthesis, histidine metabolism, pyrimidine metabolism, tryptophan metabolism, vitamin B6 metabolism, arginine and proline metabolism. Conclusions: ELITEA compound tea can effectively reduce the serum uric acid levels in HUA model rats. Based on the in-depth analysis of untargeted metabolomics, ELITEA compound tea mainly regulates the arginine biosynthesis pathway by modulating three important metabolites, arginine, glutamate, and ornithine, to reduce serum uric acid.